Negative Marking in Online Sales Portal - Palani Raj, K.; Veeramani, G. (International Journal of Engineering and Technology, 2018)
Negative marking is provided to the sellers in online portals. It is to avoid unnecessary problems for customers because of sellers in online portal. There are different factors considered for providing negative marking to sellers. Quality of product is improved because of that and it increases the customer satisfaction and hence increases the sales in online portal. There are possibilities for selling defective products and delay in delivery of products in online portal. Since the customers are not contacting the sellers directly, there are more possibilities for such errors. Negative marking plays a vital role in online marketing to help the customers to buy the products with confidence. In this research paper, a deep analysis of negative marking is carried out to understand the effects of negative marking in online sales.Â Â